2007
DOI: 10.1002/ana.21190
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal LR11/sorLA expression is reduced in mild cognitive impairment

Abstract: Objective-LR11 (aka sorLA) is a multifunctional neuronal receptor that binds apolipoprotein E and interacts with amyloid precursor protein to regulate amyloidogenesis. Reduced expression of LR11, as occurs in the brains of individuals with Alzheimer's disease (AD), increases amyloidogenesis, and variants in the gene that encodes LR11, SORL1, have recently been linked to risk for late-onset AD. In this study, we sought to determine whether reduced expression of LR11 occurs early in the disease process and wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 56 publications
4
76
3
Order By: Relevance
“…For instance, reduced levels of SORLA in cortex and hippocampus, but not in cerebellum (a tissue that is not affected by AD pathology), have been previously noted in autopsy material from AD patients (Scherzer et al, 2004). Subsequent studies also documented poor receptor expression in individuals with mild cognitive impairment (Sager et al, 2007).…”
Section: Sorla a Neuronal Trafficking Receptor Implicated In Admentioning
confidence: 87%
See 1 more Smart Citation
“…For instance, reduced levels of SORLA in cortex and hippocampus, but not in cerebellum (a tissue that is not affected by AD pathology), have been previously noted in autopsy material from AD patients (Scherzer et al, 2004). Subsequent studies also documented poor receptor expression in individuals with mild cognitive impairment (Sager et al, 2007).…”
Section: Sorla a Neuronal Trafficking Receptor Implicated In Admentioning
confidence: 87%
“…Most studies on brain or cerebrospinal fluid specimens reported an ,20-50% decrease in the levels of SORLA in the brain of some individuals with sporadic AD (Scherzer et al, 2004;Andersen et al, 2005;Dodson et al, 2006;Sager et al, 2007;Zhao et al, 2007). A recent study failed to recapitulate the reduced expression of SORLA in yet another set of post-mortem AD brain samples (Sager et al, 2012), and, therefore, additional studies might be necessary to resolve this issue.…”
Section: Sorla a Neuronal Trafficking Receptor Implicated In Admentioning
confidence: 99%
“…172) Interestingly, the expression level of SorLA is decreased in sporadic AD but not in familial AD. 173,174) SorLA levels are also reduced in neurons of patients with mild cognitive impairment 175) and in the CSF of patients with late-onset AD. 176) SorLA regulates APP sorting in neurons and protects the neurons from amyloidgenic cleavage of APP by b-secretase at Golgi.…”
Section: Lipid Metabolism and Admentioning
confidence: 97%
“…SORL1 mediates the transport of vesicles from the cell surface to the Golgi apparatus and endoplasmic reticulum, which is vital in APP processing. According to Sager et al (43), decreased SORL1 expression levels reflects cognitive performance and may predispose individuals with mild cognitive impairment to the development of AD (43). Recently Louwersheimer et al (44) demonstrated that SORL1 SNP rs2070045G allele was correlated with hippocampal atrophy and CSF-tau, suggesting the role of SORL1 in AD pathology.…”
Section: Sortilin-related Receptor (Sorl1)mentioning
confidence: 99%